UMPSA Researcher Assoc. Prof. Dr. Mohd Faizal develops Virtual Reality-Based Cyber Training - Nur Hartini, Mohd Hatta (UMPSA, 2025)
PEKAN, 6 August 2025 – Recognising that conventional cybersecurity training often has limited impact due to the lack of realistic simulation elements, a research team from the Faculty of Computing (FK), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), led by Assoc. Prof. Dr. Mohd Faizal Ab Razak, has developed CyberSecure VR—an immersive and interactive virtual reality (VR)-based training system.